2016
DOI: 10.1016/j.canlet.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomic and functional analysis of human oral squamous cell carcinoma cell lines reveals synergistic effects of FAT1 and CASP8 inactivation

Abstract: Oral squamous cell carcinoma (OSCC) is genetically highly heterogeneous, which contributes to the challenges of treatment. To create an in vitro model that accurately reflects this heterogeneity, we generated a panel of HPV-negative OSCC cell lines. By whole exome sequencing of the lines and matched patient blood samples, we demonstrate that the mutational spectrum of the lines is representative of primary OSCC in The Cancer Genome Atlas. We show that loss of function mutations in FAT1 (an atypical cadherin) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 33 publications
2
43
0
Order By: Relevance
“…As the most compelling novel driver gene for penile cancer, caspase 8 is an apoptosis‐inducing cysteine protease that is activated through the formation of a death‐inducing signaling complex when death receptors are complexed to their specific ligands, such as TRAIL, TNF‐α and Fas. Previous studies showed that CASP8 has been implicated in cancer risk in relation to multiple other cancers, including oral squamous cell carcinoma . In this study, the function of CASP8 has been further confirmed to be closely related to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the most compelling novel driver gene for penile cancer, caspase 8 is an apoptosis‐inducing cysteine protease that is activated through the formation of a death‐inducing signaling complex when death receptors are complexed to their specific ligands, such as TRAIL, TNF‐α and Fas. Previous studies showed that CASP8 has been implicated in cancer risk in relation to multiple other cancers, including oral squamous cell carcinoma . In this study, the function of CASP8 has been further confirmed to be closely related to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was repeated three times **p < 0.01, ****p < 0.0001. ligands, such as TRAIL, TNF-α and Fas. Previous studies showed that CASP8 has been implicated in cancer risk in relation to multiple other cancers, 33,34 including oral squamous cell carcinoma. 34 In this study, the function of CASP8 has been further confirmed to be closely related to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We are particularly interested in the heterogeneous group of Head and Neck Squamous cell Carcinomas (HNSCs) as these account for a large number of mortalities each year in the Indian subcontinent (2,3). Multiple exome sequencing studies have revealed the landscape of recurrent somatic mutations in HNSCs and its prevalent subtype of Oral Squamous Cell Carcinomas (OSCCs) (4)(5)(6)(7)(8). While TP53 was the most significant recurrently mutated gene in this cancer type, several other genes such as CASP8, FAT1, and NOTCH1 were also unearthed as significantly recurrently mutated by these large-scale sequencing studies.…”
Section: Introductionmentioning
confidence: 99%
“…Barring TP53, the roles of these genes in oral epithelium homeostasis, and how this is altered owing to their mutation in cancer remain to be fully elucidated (9). In this study, we chose to focus on the CASP8 gene, which is mutated in ~10% of all HNSC cases, and more specifically in 34% of cases with OSCC of the gingiva-buccal sulcus (OSCC-GB), the subtype that accounts for the majority of HNSC cases in the Indian subcontinent (4,7,8). The types of mutations in CASP8 reported in these HNSC cases included loss of function due to frameshift, nonsense mutation or splice mutation as well as missense and deletion mutations.…”
Section: Introductionmentioning
confidence: 99%
“…We are particularly interested in the heterogeneous group of Head and Neck Squamous cell Carcinomas (HNSCs) as these account for a large number of mortalities each year in the Indian subcontinent. Multiple exome sequencing studies have revealed the landscape of recurrent somatic mutations in HNSCs and its prevalent subtype of Oral Squamous Cell Carcinomas (OSCCs) [1][2][3][4][5]. While TP53 was the most significant recurrently mutated gene in this cancer type, several other genes such as CASP8, FAT1, and NOTCH1 were also unearthed as significantly recurrently mutated by these large-scale sequencing studies.…”
Section: Introductionmentioning
confidence: 99%